2005
DOI: 10.1152/ajplung.00234.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary abnormalities due to ABCA1 deficiency in mice

Abstract: Ϫ/Ϫ ) have been shown to have low-serum high-density lipoprotein and abnormal lung morphology. We examined alterations in the structure and function of lungs from Ϫ/Ϫ mice (DBA1/J). Electron microscopy of the diseased mouse lung revealed areas of focal disease confirming previous results (47). Lipid analysis of the lung tissue of Ϫ/Ϫ mice showed a 1.2-and 1.4-fold elevation in total phospholipid (PL) and saturated phosphatidylcholine, respectively, and a marked 50% enrichment in total cholesterol content predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
100
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 65 publications
7
100
2
2
Order By: Relevance
“…These include GM-CSF, SP-B, SP-C, SP-D, ABCA3, ABCA1, and LAL (11)(12)(13)(14)(15)(16)(17)(18). Together, these reports illustrate the important roles of pulmonary macrophages and pneumocytes type 2 in regulating lipid, and especially surfactant, metabolism.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These include GM-CSF, SP-B, SP-C, SP-D, ABCA3, ABCA1, and LAL (11)(12)(13)(14)(15)(16)(17)(18). Together, these reports illustrate the important roles of pulmonary macrophages and pneumocytes type 2 in regulating lipid, and especially surfactant, metabolism.…”
Section: Discussionmentioning
confidence: 85%
“…Nonetheless, we conclude that Abcg1 Ϫ/Ϫ type 2 cells retain the capacity to secrete surfactant since surfactant levels (recovered after BAL) increased ϳ5-fold and tubular myelin is present in the alveolar hypophase of Abcg1 Ϫ/Ϫ mice. Recent studies have linked mutations in ABCA3 (13) or ABCA1 (17) to respiratory distress syndrome and altered surfactant secretion in humans and mice, respectively. Thus, the decrease in Abca3 that occurs in the lungs of Abcg1 Ϫ/Ϫ mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a role for ABCG1 in pulmonary function was discovered (24). The lung phenotype of older (8 mo of age) Abcg1 Ϫ/Ϫ mice is similar to that observed for Abca1 Ϫ/Ϫ mice (25). The deletion of ABCG1 or ABCA1 leads to progressive lipid accumulation and cellular accumulation in the lung (24).…”
mentioning
confidence: 77%
“…Taken together, these studies identified pivotal roles for ABCG1 in controlling pulmonary homeostasis in vivo (20,22). Interestingly, based on gene deletion in mice and/or natural mutations in humans, other members of the ABC family of transporters, ABCA1, ABCA3, and ABCC7, have also been shown to play important roles in pulmonary physiology (23)(24)(25)(26)(27).…”
mentioning
confidence: 94%